Educating for Peace and Pluralism: The Implementation of Multicultural Religious Values in Indonesian Religious Education - Mukhlisin; Cikusin, Yaqub; Ghony, Djunaidi (International Journal of Scientific Research and Management (IJSRM), 2025)
This study explores the implementation of multicultural religious values in Indonesian religious education, emphasizing the importance of tolerance, mutual respect, interfaith dialogue, inclusivity, and justice. Through a qualitative literature review, the research analyzes policy documents, theoretical frameworks, and empirical studies to assess how these values are integrated into classroom practices. Findings reveal that while national initiatives such as Moderasi Beragama have successfully promoted tolerance and mutual respect, significant challenges persist in advancing interfaith dialogue, inclusive curricula, and equitable practices. These obstacles include inadequate teacher training, outdated learning materials, and resistance from conservative groups. The study highlights a critical gap between policy frameworks and pedagogical realities, stressing the need for systemic reforms. Key recommendations include enhancing teacher education, updating curricula, institutionalizing interfaith dialogue, and fostering collaboration among stakeholders to build a more inclusive, peaceful educational environment in Indonesia.